EVALUATION OF MINE SUMP AT PT. BERKAT ANUGERAH SEJAHTERA, PT. ANTANG GUNUNG MERATUS SITE, SOUTH KALIMANTAN: EVALUASI MINE SUMP PADA PT. BERKAT ANUGERAH SEJAHTERA SITE PT. ANTANG GUNUNG MERATUS KALIMANTAN SELATAN - Ismail, Ardhan; Winonazada, Rety; Pontus, Albertus (Jurusan Teknik Pertambangan Program Studi S1 Teknik Pertambangan Fakultas Teknik Pertambangan dan Perminyakan Universitas Papua, 2024)
PT. Berkat Anugerah Sejahtera (PT. BAS) is one of the mining contractors operating at PT. Antang Gunung Meratus in South Kalimantan. In its operations, one of the main challenges is the entry of water into the mining pit and managing surface runoff that flows into the mining front. The water entering the pit needs to be properly managed so it can be controlled and concentrated at a single point, referred to as the lowest point. This water management is carried out by constructing a sump or a collection point at the lowest location. The purpose of this study is to understand the dewatering process and measure the runoff volume entering the mine, assess the actual sump capacity, and evaluate the efficiency of the pumping system. Data collection was conducted to compare the planned sump capacity with the actual sump capacity in the field. Rainfall data from the past 10 years were analyzed to determine rainfall intensity and calculate the catchment area of PT. BAS, which spans 121.18 hectares. From this, the runoff volume was calculated to be 25,230.53 m³/day. The study found that the actual sump capacity is 32,215 m³. However, this capacity is likely insufficient to accommodate the total runoff volume entering the mine, suggesting the need for further evaluation of the current sump capacity to improve water management efficiency at the mining site.